Design of Asymmetric Parallel-Cascaded Micro-Ring Resonator Using Transfer Matrix and Signal Flow-Graph Methods - Dadin Mahmudin; Pamungkas Daud; Yusuf Nur Wijayanto (National Research and Innovation Agency, 2013)
Asymmetric parallel-cascaded micro-ring resonator (APCMR) is proposed. The proposed device is composed of two or more micro-ring-resonators with different diameter. The proposed device is designed using transfer matrix combined with signal flow graph methods. The designed device with crosstalk less than and equal -10 dB can be obtained by setting coupling coefficient. The proposed device can be used for optical filters and sensors.